2018
DOI: 10.1146/annurev-ento-020117-043049
|View full text |Cite
|
Sign up to set email alerts
|

Pseudacteon Phorid Flies: Host Specificity and Impacts on Solenopsis Fire Ants

Abstract: Human commerce has resulted in the spread of the imported fire ants, Solenopsis species, worldwide. Six species of parasitic Pseudacteon phorid flies that are highly host specific to the Solenopsis saevissima complex of Solenopsis fire ants have been successfully released in the southern United States. The presence of Pseudacteon phorid flies, in addition to having direct mortality effects on their host ants, modifies foraging behavior and disrupts interspecific competition between host species and other ant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 134 publications
(248 reference statements)
1
27
0
Order By: Relevance
“…This information could help when rearing parasitoids, for example by separating the preferred ant sizes with sieves before oviposition. A similar pattern was detected for Pseudacteon parasitoids, specialists of Solenopsis ants (Chen & Fadamiro, 2018). Folgarait et al (2005) proposed that there is a minimum head size that allows phorid developmenthere we showed that non-viable pupae of A. ambiguus and A. heyeri from Corrientes were found in significantly smaller head sizes than viable ones.…”
Section: Discussionsupporting
confidence: 85%
“…This information could help when rearing parasitoids, for example by separating the preferred ant sizes with sieves before oviposition. A similar pattern was detected for Pseudacteon parasitoids, specialists of Solenopsis ants (Chen & Fadamiro, 2018). Folgarait et al (2005) proposed that there is a minimum head size that allows phorid developmenthere we showed that non-viable pupae of A. ambiguus and A. heyeri from Corrientes were found in significantly smaller head sizes than viable ones.…”
Section: Discussionsupporting
confidence: 85%
“…At least 36 Pseudacteon phorid species parasitize Solenopsis invicta and Solenopsis saevissima; 17 phorid species attack Solenopsis invicta alone (reviewed in Chen and Fadamiro, 2018). The small Pseudacteon flies are attracted to disturbed fire ant mounds and hover above distressed and alarmed ants.…”
Section: Parasitoids Of Workersmentioning
confidence: 99%
“…(Blum and Brand, 1972). While work centered on host ant preference by various associates is important foundational research [e.g., Eucharitidae wasps (Murray et al, 2013); Paussus ant-nest beetles (Moore and Robertson, 2014); phorid flies (Mathis and Philpott, 2012;Chen and Fadamiro, 2018); social parasites (Lenoir et al, 2001;Buschinger, 2009)], this hypothesis shifts the focus to the associate community where network-based analyses will prove useful (Ivens et al, 2016). In order to investigate this hypothesis, we must begin with host lineages having (1) a well-resolved phylogeny, (2) a well-studied communication system, and (3) numerous known associates.…”
Section: Extant Species-rich Host Lineagementioning
confidence: 99%
“…Pseudacteon decapitating flies are specific parasitoids of ants [1]. At least 22 species of Pseudacteon flies are known to attack South American fire ants in the Solenopsis saevissima (Smith) complex [2][3][4]. Seventeen species are parasitoids of the black imported fire ant, Solenopsis richteri, and the red imported fire ant, Solenopsis invicta [2].…”
Section: Introductionmentioning
confidence: 99%
“…At least 22 species of Pseudacteon flies are known to attack South American fire ants in the Solenopsis saevissima (Smith) complex [2][3][4]. Seventeen species are parasitoids of the black imported fire ant, Solenopsis richteri, and the red imported fire ant, Solenopsis invicta [2]. These fly species are specific to S. saevissima complex fire ants and do not occur in populations of Solenopsis geminata complex fire ants native to North and Central America [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%